Propuesta de manejo y conservación de la Reserva Ecológica Privada Tamandua mediante su zonificación y valoración ambiental - Sarmiento Rosero, Nataly Gabriela (2022)
This research was carried out in the Tamandua Private Ecological Reserve, with an area of 70.00 ha, located in the province of Pastaza, Santa Clara canton, San José parish, Samasunchi sector. In the study, the conservation status of the area was identified and a Rapid Ecological Assessment (EER) was carried out, to identify sites of high ecological interest that contain relevant ecological characteristics, in addition, the zoning of the entire area was carried out to issue ordinance guidelines. and compliance with the management objectives of the reserve, ensuring its conservation areas and promoting the sustainability of its resources\; Finally, a Management Plan was drawn up with programs and subprograms aimed at serving as a guide for management and conservation, through actions that help the Reserve to mitigate, prevent and offset possible effects and impacts that it may suffer in the future. As the most relevant results of the diagnosis, it was known that the Reserve is located within the Piemontano Evergreen Forest Terrestrial Ecosystem of the North of the Eastern Cordillera of the Andes that cover elevational levels from 874 masl to 1,013 masl. From the floristic analysis, species in conservation status were determined with Near Threatened (NT) categories such as Cinnamon (Ocotea quixos), Uksha (Geonoma macrostachys) and two classes of ferns: Salpichlaena Volubilis and Selaginella Arthritica. There was also a species in a vulnerable conservation status Heliconia obscura and a species in the Endangered category (EN), such as the species Elephant's Ear (Alocasia Lauterbachiana). Regarding the vegetation cover analysis, the sande species (Brosimum utile) was found with the highest Dominance value (16.7), however\; The Importance Value Index (IVI) placed the Guadua species (Guadua angustifolia) with a value of 37.6 as the most important species.